2013
DOI: 10.1111/jcpe.12147
|View full text |Cite
|
Sign up to set email alerts
|

Destructive periodontal disease in adult Indians from Northeast Brazil: cross‐sectional study of prevalence and risk indicators

Abstract: Though periodontitis was highly prevalent in Kiriri Indians, only few teeth showed advanced disease, and periodontitis was associated with higher age, male sex and diabetes. A public health action that includes programs of prevention and treatment targeting high-risk groups is vital to improve the periodontal status of this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
57
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 29 publications
0
57
0
5
Order By: Relevance
“…Inequalities in unmet dental needs are particularly evident in Indian groups 14 and in other racial and/or ethnic minorities 15 . However, knowledge of tooth-loss frequency and its risk factors in Indian populations is scarce because of logistical, financial and political constraints 16 . A single study evaluated tooth loss in 12,349 American Indian and Alaska Native adults.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inequalities in unmet dental needs are particularly evident in Indian groups 14 and in other racial and/or ethnic minorities 15 . However, knowledge of tooth-loss frequency and its risk factors in Indian populations is scarce because of logistical, financial and political constraints 16 . A single study evaluated tooth loss in 12,349 American Indian and Alaska Native adults.…”
Section: Introductionmentioning
confidence: 99%
“…At the time of this writing, the Brazilian government recognised 240 Indian tribes, who comprised around 900,000 people (or 0.4% of Brazil's population). The Kiriri Indians live in north-east Brazil and comprise an isolated population of approximately 2,182 16 . Access to the area inhabited by this population is challenging, and external influences are limited, as shown by maintenance of the social, cultural and behavioural backgrounds of the population 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, researchers have not reached a consensus on a PMPE protocol to be used for large scale epidemiological studies, leading to the use of different methods to measure periodontitis (Figueiredo et al. , Tu et al. ).…”
mentioning
confidence: 99%
“…Although several PMPE protocols produced small biases for estimates of disease severity (Kingman et al 2008) and extent (Owens et al 2003); they have shown various degrees of underestimation of disease prevalence (Susin et al 2005, Vettore et al 2007, Eke et al 2010. Therefore, researchers have not reached a consensus on a PMPE protocol to be used for large scale epidemiological studies, leading to the use of different methods to measure periodontitis (Figueiredo et al 2013, Tu et al 2013.…”
mentioning
confidence: 99%